Karakteristik Pemikiran Hassan Hanafi dan Rekonstruksinya terhadap Ushul al-Fiqh dalam kitab Min al-Nas ila al-Waqi - Ardian Al Hidaya (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
The emergence of Islamic thinkers who try to give a new 'touch' in paradigms and methodologies to develop scientifically and responsibly in Islamic studies such as Hassan Hanafi, deserves appreciation. He came here by concentrating on the project of Islamic tradition (tura>th) which he packaged in the slogan al-Tura>th wa al-Tajdi>d, which he took in three general steps, namely 1) Examining our classical traditions to find out how we behave and positioning against our classical tradition (Mawqifuna> min al-Tura>th al-Qadi>m), 2) Examining the Western tradition to find out how we behave and position ourselves in the Western tradition (Mawqifuna> min al- Tura>th al-Gharby, and 3) Performing interpretations (Naz}riyah al-Tafsi>r). One of the branches of Hassan Hanafi's tradition renewal project is the reconstruction of us}u>l al-fiqh. For him, us}u>l al-fiqh is the science of 'tanzi>l'; ie 'something' that comes from God to man. Science that is oriented downwards, towards the mas}lah}ah of mankind. The characteristics of us}u>l al- fiqh ala Hassan Hanafi have four aspects: First, resistematization of the object of discussion. Starting from al-Mas}a>dir al-Arba'ah, then al-Adillah al- Shar'iyyah then al-Ah}ka>m al-Shar'iyyah. Second, there is an orientation and tendency to provide wide space for the transparency of tasks and human potential. Third, provide idioms that articulate the potential of humanity. Fourth, it is deductive in nature, formulating general theories without examples of legal cases.